Air Pollution in China - Liu, Duanyang; Qin, Kai; Wang, Honglei (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In China, serious air pollution has been apparent since the 1990s, and this is complicated due to human activities and partly due to natural factors. It is worth mentioning that local air pollution has greatly improved in the past 5 years, mainly due to the progress of institutional and technical measures since the 2010s. However, the appearance of air pollution in China is changing, as the compound pollution of photochemical pollution and aerosol pollution has been formed, and air pollution control has entered a new phase. In order to record the Chinese atmospheric environment's development with the passage of time and to identify what we are going to face in the future, we invite papers in our latest Special Issue, "Air Pollution in China", which will focus on air pollution trends throughout China or in each region of China over the past 30 years, the effects of countermeasures, analysis of the latest atmospheric environment, etc.